COVID-19 and assisted reproductive technology services: repercussions for patients and proposal for individualized clinical management - Carlo Alviggi; Sandro C. Esteves; Raoul Orvieto; Alessandro Conforti; Antonio La Marca; Robert Fischer; Claus Y. Andersen; Klaus Bühler; Sesh K. Sunkara; Nikolaos P. Polyzos; Ida Strina; Luigi Carbone; et al. (BMC, 2020)
Abstract The prolonged lockdown of health services providing high-complexity fertility treatments -as currently recommended by many reproductive medicine entities- is detrimental for society as a whole, and infertility patients in particular. Globally, approximately 0.3% of all infants born every year are conceived using assisted reproductive technology (ART) treatments. By contrast, the total number of COVID-19 deaths reported so far represents approximately 1.0% of the total deaths expected to occur worldwide over the first three months of the current year. It seems, therefore, that the number of infants expected to be conceived and born -but who will not be so due to the lockdown of infertility services- might be as significant as the total number of deaths attributed to the COVID-19 pandemic. We herein propose remedies that include a prognostic-stratification of more vulnerable infertility cases in order to plan a progressive restart of worldwide fertility treatments. At a time when preventing complications and limiting burdens for national health systems represent relevant issues, our viewpoint might help competent authorities and health care providers to identify patients who should be prioritized for the continuation of fertility care in a safe environment.